1991
DOI: 10.1093/oxfordjournals.aje.a116079
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure, the Prevalence of Cardiovascular Diseases, and Exposure to Cadmium: A Population Study

Abstract: In a population study conducted from 1985 to 1989 in Belgium, the authors investigated whether exposure to cadmium is associated with blood pressure elevation and with an increased prevalence of cardiovascular diseases. The participants, aged 20-88 years, constituted a random sample of the households living in two low exposure areas (n = 803) and two high exposure areas (n = 1,283). For each exposure level, a rural and an urban district were selected. The cadmium levels in blood (8.5 vs. 11.0 nmol/liter) and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 0 publications
2
26
3
Order By: Relevance
“…High cadmium concentrations have recently been associated with a rise in blood pressure in subjects from Finland (30). However, our data are in agreement with results obtained by other authors (12)(13)(14)(15), even for samples of the general population living in areas with a higher environmental exposure to cadmium (15,31,32). a Regression coefficients obtained after the last step of the multiple regression analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…High cadmium concentrations have recently been associated with a rise in blood pressure in subjects from Finland (30). However, our data are in agreement with results obtained by other authors (12)(13)(14)(15), even for samples of the general population living in areas with a higher environmental exposure to cadmium (15,31,32). a Regression coefficients obtained after the last step of the multiple regression analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Animal studies have put into evidence that long-term exposure to cadmium at low levels can induce an increase in blood pressure (6 -8). However, conflicting results have been reported in humans and both negative (9 -11) and positive conclusions (12)(13)(14)(15) have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Cd levels found in blood (0.96Ig/L vs. 1.24Ig/L respectively) were significantly (p<0.001) raised in the two high exposure areas compared with the two low exposure areas (p<0.001) [67]. This indicates that, despite levels in this study not being high enough to be deemed chronic occupational exposure, there may be higher environmental exposure in the Pacific Islands group at 1.15Ig/L (0.98-1.36) ( Table 1).…”
Section: Ethnic Differences In Exposure To Trace Elementsmentioning
confidence: 83%
“…A Belgian study tested blood Cd levels from both low and high environmental exposure areas [67]. Cd levels found in blood (0.96Ig/L vs. 1.24Ig/L respectively) were significantly (p<0.001) raised in the two high exposure areas compared with the two low exposure areas (p<0.001) [67].…”
Section: Ethnic Differences In Exposure To Trace Elementsmentioning
confidence: 99%
“…It has been well documented among the general population that the urinary excretion of cadmium is positively associated with the urinary excretion of calcium (Baecklund et al 1999). In the CadmiBel study, Staessen and colleagues (Staessen et al 1991a(Staessen et al , 1991b(Staessen et al , 1993(Staessen et al , 1999 showed that after adjustment for confounders, doubling of the urinary cadmium excretion was associated with a 0.25-mmol rise per day in urinary calcium excretion. Similarly, in their cohort of Swedish women, Järup et al (1998b) recently documented a 90% increase in urinary calcium excretion among those whose urinary cadmium concentration was > 1 nmol/mmol creatinine (Staessen and Lauwerys 1993).…”
Section: U-cdmentioning
confidence: 99%